An interactive approach for placing alternatives in preference classes - Köksalan, Mustafa Murat; Ulu, C (European Journal of Operational Research, 2003)
In this paper, we consider the multiple criteria decision making problem of partitioning alternatives into preference classes. We develop an interactive procedure based on the assumption that the decision maker (DM) has a linear utility function. The approach requires the DM to place an alternative in a preference class from time to time. Based on the preference information derived from the DM's placement as well as from dominance and linearity, we try to place other alternatives. We present results on the performance of the algorithm applied to four different sets of alternatives.